A cross-sectional study: Assessment of optimal breastfeeding practices among tribal women having children 0–23 months of age residing in an Island of Sundarbans, West Bengal - A S Reshma; Lina Bandyopadhyay; Bobby Paul; Aditi Ajit Jaiswal; Arpita Das; Niladri Sekhar Pal (Journal of Surgical Specialties and Rural Practice, 2023)
Context: Tribal population is vulnerable to all inequities of the society and less penetrated by the service providers. Breastfeeding, 0–23 months old children is important for their development and is boon for their health. Objective: The objective of this study is to estimate the prevalence of optimal breastfeeding practices (OBFs) and elicit its predictors. Materials and Methods: This descriptive cross-sectional study was conducted in the tribal area of Sunderbans, West Bengal, among mothers having children 0–23 months of age, from May 2021 to September 2021. Participants were selected by the cluster sampling technique. OBFs were assessed by initiation of breastfeeding within 1 h of birth, exclusive breastfeeding till 6 months of age, and continuation of breastfeeding along with complementary feed till 23 months of age. Iowa Infant Feeding Attitude Scale was administered to assess attitude toward breastfeeding. Statistical analysis was done using multivariable logistic regression. Results: The mean age of the study participants was 24.8 ± 4.1 years. Early initiation of breastfeeding was done by 76.5% of the participants, but continuation beyond 6 months of age by 70.9%. OBFs were shown by 25.5% of the participants, which has a significant association with the knowledge about the breastfeeding practices (adjusted odds ratio [aOR]: 2.14; 95% confidence interval [CI]: 1.52–3.01) and maternal education (aOR: 3.78; 95% CI: 1.17–12.17). Conclusion: This study showed that only one-fourth of the participants have OBFs. This situation must be addressed with imparting proper knowledge about the importance of breastfeeding. Support group of women in the community should be formulated to aid mothers in continuation of breastfeeding.